2020
DOI: 10.1115/1.4047887
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Investigation of the Impact of Multiple Injection Strategies on Combustion Efficiency in Diesel–Natural Gas Dual-Fuel Low-Temperature Combustion Engines

Abstract: Dual fuel diesel-methane low temperature combustion (LTC) has been investigated by various research groups, showing high potential for emissions reduction (especially oxides of nitrogen (NOx) and particulate matter (PM)) without adversely affecting fuel conversion efficiency in comparison with conventional diesel combustion. However, when operated at low load conditions, dual fuel LTC typically exhibits poor combustion efficiencies. This behavior is mainly due to low bulk gas temperatures under lean conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The differences may have been caused by the close-coupled (or short-dwell) strategy chosen in the present work for multiple injections and the relatively lower PES conditions chosen for the rail pressure sweep. For example, Bartolucci et al [30] observed a decrease in the CO emissions for higher rail pressures, albeit for a long dwell between the multiple injections as opposed to close-coupled multiple injections used in the present work. In a similar fashion, Hariharan et al [31] showed an improvement in the efficiency-emissions tradeoffs when increasing the rail pressure.…”
Section: Step 4: Rail Pressure Sweepmentioning
confidence: 61%
See 2 more Smart Citations
“…The differences may have been caused by the close-coupled (or short-dwell) strategy chosen in the present work for multiple injections and the relatively lower PES conditions chosen for the rail pressure sweep. For example, Bartolucci et al [30] observed a decrease in the CO emissions for higher rail pressures, albeit for a long dwell between the multiple injections as opposed to close-coupled multiple injections used in the present work. In a similar fashion, Hariharan et al [31] showed an improvement in the efficiency-emissions tradeoffs when increasing the rail pressure.…”
Section: Step 4: Rail Pressure Sweepmentioning
confidence: 61%
“…Rail pressure has been shown to impact dual-fuel emissions in the literature [30,31]. The AHRR and emissions values for both fueling combinations are shown in Figure 18.…”
Section: Step 4: Rail Pressure Sweepmentioning
confidence: 99%
See 1 more Smart Citation